Agri-food exports in the enlarged European Union - Alessandro ANTIMIANI; Anna CARBONE; Valeria COSTANTINI; Roberto HENKE (Agricultural Economics (AGRICECON), 2012)
This paper explores the agri-food export dynamics in the New Member States and the Old Member States of the European Union during the enlargement process. The analysis relies on two different approaches based on the similarity and the sophistication indices of exported goods using a disaggregation at 95 items. The analysis shows that different and somehow divergent paths are in place. On the one side, the Czech Republic and Poland are involved in a quality catching up process and increase their competitiveness. On the other side, Bulgaria and Romania seem to be still trapped in the low-quality segment of the agri-food market with a decreasing competitiveness performance in the richest segment of the European market.